Test system for the detection of binding antibodies to interferon beta-1a for clinical use - E. A. Kuzminova; T. Yu. Ostroukhova; A. V. Grachev; E. L. Morozova (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Test system for determining the presence of binding antibodies to interferon beta-1a (BAB to IFN beta-1a) in serum using ELISA has been developed. The validation included sensitivity, selectivity, specificity, precision and accuracy, robustness, stability, suitability of the test system studies. The applicability of the mentioned test system has been approved for the use in clinical studies for the evaluation of interferon beta-1a immunogenicity (pegylated and non-pegylated forms).